Shortcomings, limitations and gaps in physiological roles of extracellular vesicles in obesity - Valero, Paola; Silva, Katherin; Valenzuela-Hinrichsen, Andrés; Vásquez, Antonia; Espinoza, Fernanda; Lira, Fernanda; Cornejo, Marcelo; Fuentes, Gonzalo; González, Daniel; Moore-Carrasco, Rodrigo; van der Beek, Eline M.; Hillebrands, Jan-Luuk; et al. (Wiley, 2024)
Extracellular vesicles (EVs) play a crucial role in mediating communication between cells across species and kingdoms. The intercellular communication facilitated by EVs through autocrine and paracrine signalling mechanisms is essential for cell survival, maintaining normal metabolic functions and ensuring overall bodily homeostasis and health. Extracellular vesicles are present in various bodily fluids, such as pleural effusions, plasma, breast milk, amniotic fluid, semen and saliva. Additionally, the generation and release of EVs contribute to the removal of cellular waste. Patients with obesity exhibit a higher release and amount of circulating EVs than individuals with normal weight. This increased EV release in obesity might contribute to the inflammatory state characteristic of this metabolic condition, because higher levels of pro-inflammatory molecules are found within their cargo. However, interpreting results related to EV abundance, cargo and biological actions can be complicated by several factors; these include variations in cell sources, a wide age range (from children to the elderly), a mix of females and males, medication use and health status, a range of body weights (from normal weight to morbid obesity) and differences between in vitro assays using cell lines versus primary cultures. This article addresses the shortcomings, limitations and gaps in knowledge, providing a framework for enhancing our understanding of the physiological effects of EVs on obesity. (Figure presented.).
Keywords: age; exosomes; extracellular vesicles; human; obesity; sex